Using Cornell Note-Taking to Improve Listening Comprehension - Khusna Maulidia; Samsul Bahri Ys; Tengku Maya Silviyanti (Research in English and Education Journal, 2021)
The objective of this study is to find out whether the use of Cornell note taking improves students’ listening skill to the second semester students of English Study Program at Syiah Kuala University, Banda Aceh. The sample of this study consisted of 23 students of Unit 3, Listening Class. Purposive sampling was used to determine the sample. This study was designed as an experimental quantitative research with one group pre-test and post-test scheme. Written tests (pre-test and post-test) were used to collect the data. Then, statistical formula was used to analyze the data. The study result showed that the mean score of students’ pre-test score was 54.78 and post-test was 64.93. The t-score was 3.27 and t-table was 2.073873. It can concluded that the t-score was higher than t-table. Therefore, the alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected. So, the use of Cornell note taking improves students’ listening skill.